EFL SPEAKING PRACTICE ASSISTED BY ZOOM APPLICATION DURING COVID-19 OUTBREAK IN INDONESIA - Angela Bayu Pertama Sari; Dwi Iswahyuni (Universitas Sarjanawiyata Tamansiswa, 2021)
Abstract A few studies have investigated Zoom application for EFL speaking practice during this covid-19 outbreak. Still, there are minimal studies that compare speaking practice assisted by Zoom with face-to-face speaking practice. Thus, this study aimed to find out students’ preference of face-to-face speaking practice compared with Zoom-assisted speaking practice and the suggestions to meet the ideal speaking practice during the Covid-19 outbreak. The research method employed in this study was descriptive qualitative research in which it used open-ended questionnaires to gather data. The results showed that 61% of the students liked face-to-face speaking practice due to social interaction, the more comfortable atmosphere, practicality (no time constraint and no internet connection issue), and support for self-improvement (improving confidence, getting more knowledge, and easier to understand). Furthermore, some suggestions related to Zoom-assisted speaking practice were to make it shorter, be on time, and give more variation on discussion topics. In summary, face-to-face speaking practice is more preferred than Zoom-assisted speaking practice. Moreover, the suggestions to meet the ideal speaking practice during the covid-19 outbreak include Zoom with some class regulations that can save more internet data and make it more exciting. Keywords: EFL; speaking; Zoom application; Covid-19; pandemic